Media globalisation and the responses of the Nigerian broadcast media (2004)
The globalisation of the media of mass communication has been praised for being one of the major catalysts for the spread of democracy and development especially in the developing world. But discussions of the impact of media globalisation have by no means been homogenous. There are strong arguments that rather than being beneficiaries, democracy and development have been victims of the globalized media world. As a result, nations and institutions are responding to media globalisation with caution. This paper examines the possible impact of global media on Nigerian democracy and development. It attempts to categorise the responses of the Nigerian broadcast media to media globalisation as reflected in how they handle products of global media. Four such categories were discovered: acceptance, replication, metacasting and blackout. The paper discusses the implications of these for our democracy and development.